Salivary Alpha Amylase Enzyme and Calcium Changes with the Age and Their Effect on Dental Caries - Haider A Naji (Journal of Global Pharma Technology, 2018)
Introduction: Saliva is a clear, slightly acidic oral secretion, mainly produced by the major and minor salivary glands. Saliva plays an important role in the oral health and the levels of its constituents alter with age [1]. The study comprise α-amylase enzyme and Ca in saliva , and follow the changes occured in their levels according to age changes, and explain the effect of these changes on dental and periodontal tissue health. Materials &Methods: Ninety samples of saliva were collected from different age groups, which are divided into three study groups; group I (20-35 years), group II ( 36-50 years) and group III (51years and above) Amylase Alpha I and Calcium are analyzed by ELISA technique. Results: Results show that Mean ± S.D of Amylase Alpha I of the Age group I is (110.35±66.42), while that in the age group II is (71.19±58.53) and in age group III is (85.87±56.62). The level of α-amylase I among study groups is decreasing with the age, but not significant (P≥0.05). For salivary Ca, Mean & S.D of salivary calcium for the age group I is (6.04±1.87), Mean & S.D for age group II is (5.67±0.79), and for age group III is (8.07±0.56) which shows significant increasing with the age (P≤0.05). Conclusion: The level of salivary Amylase Alpha I enzyme is decreasing with age, therefore there is less adhesion of bacteria to tooth surface, while the level of salivary Ca, is increasing with age, which aid in remineralization process and reduce development of dental caries with age.Keywords: Saliva, Α-amylase enzyme, Ca.